A model for transformative learning: Individual development and social action - Group for Collaborative Inquiry (Adult Education Research Conference, 1994)
This paper explores the transformative learning process as affirming a world view grounded in an understanding of reality as permutable and interconnected. The process involves moving from cultural embeddedness through learning-in-relationship and whole person learning. An integration of phenomenology and heuristics, the research involved 132 interviews and reflections on the researchers' lived experience of the transformative learning process.